2020
DOI: 10.1016/j.sedgeo.2020.105663
|View full text |Cite
|
Sign up to set email alerts
|

Grain-size variability of point-bar deposits from a fine-grained dryland river terminus, Southern Altiplano, Bolivia

Abstract: This is a repository copy of Grain-size variability of point-bar deposits from a fine-grained dryland river terminus, Southern Altiplano, Bolivia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 99 publications
1
12
0
Order By: Relevance
“…The ubiquitous sand-sized mudstone intraclasts further demonstrate the erosive character of flows affecting the floodplain areas. The ubiquitous presence of sand-sized mudstone aggregates in fluvial deposits is attributed to the washing out of deeply cracked floodplain soils during dry periods, a process that is recognised in both modern and ancient fluvial systems (Rust and Nanson, 1989;Ekes, 1993;Gierlowski-Kordesch and Gibling, 2002;Wright and Marriott, 2007;Dasgupta et al, 2017;Simon and Gibling, 2017;Li et al, 2020). Mud-aggregate texture similar to that described here has been recognised in clay-rich soils by Fitzpatrick (1983).…”
Section: Discussionsupporting
confidence: 65%
“…The ubiquitous sand-sized mudstone intraclasts further demonstrate the erosive character of flows affecting the floodplain areas. The ubiquitous presence of sand-sized mudstone aggregates in fluvial deposits is attributed to the washing out of deeply cracked floodplain soils during dry periods, a process that is recognised in both modern and ancient fluvial systems (Rust and Nanson, 1989;Ekes, 1993;Gierlowski-Kordesch and Gibling, 2002;Wright and Marriott, 2007;Dasgupta et al, 2017;Simon and Gibling, 2017;Li et al, 2020). Mud-aggregate texture similar to that described here has been recognised in clay-rich soils by Fitzpatrick (1983).…”
Section: Discussionsupporting
confidence: 65%
“…The grain size of the lake sediments was affected by the combined effects of multiple external stresses, or the strength of the same force has large fluctuations. Although the end member model has wide applicability [57,58], it is not an effective method to conduct research in this region. Existing studies have shown that the size characteristics of lake sediments are sensitive to the regional climatic environment [59][60][61].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, recent work has shown that single‐threaded rivers are also pervasive in barren regions with a sufficient supply of fine sediment or ice (e.g. Donselaar et al ., 2013; Matsubara & Howard, 2014; Li et al ., 2015, 2020, 2022; Matsubara et al ., 2015; van Toorenenburg et al ., 2018; Ielpi, 2019; Lapôtre et al ., 2019; Santos et al ., 2019; Ielpi & Lapôtre, 2019a,b; Ielpi et al ., 2020; Levy & Cvijanovich, 2023). The absence of vegetation affects the morphodynamic processes governing channel and floodplain evolution; notably, maximum channel migration rates are almost ten times faster in such environments than in vegetated rivers of similar size (Ielpi & Lapôtre, 2020).…”
Section: Introductionmentioning
confidence: 99%